2018
DOI: 10.1029/2018jf004618
|View full text |Cite
|
Sign up to set email alerts
|

Using Persistent Scatterer Interferometry to Map and Quantify Permafrost Thaw Subsidence: A Case Study of Eboling Mountain on the Qinghai‐Tibet Plateau

Abstract: Permafrost thaw subsidence, a key indicator of permafrost degradation, remains poorly quantified or understood. It is particularly challenging to detect and measure surface subsidence due to the loss of subsurface ice over a large area because it usually develops gradually, over several years or decades. Here we utilize the persistent scatterer interferometric synthetic aperture radar (PSI) approach to remotely measure gradual surface subsidence on Eboling Mountain in the northeastern region of the Qinghai‐Tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 70 publications
(95 reference statements)
0
63
0
Order By: Relevance
“…The inversion algorithm requires a sufficient number of interferograms to estimate an appropriate trend; however, the number of high-quality interferograms is often limited in some areas. Chen et al (2018b) first applied the PS-InSAR technique to ALOS/ PALSAR data to derive permafrost thaw subsidence in the Qinghai-Tibet Plateau with a rate ranging from 0.3 to 3 cm yr −1 using 17 scenes of ALOS. SAR images acquired during the snow-covered season were used in the study, which may include errors associated with snow accumulation.…”
Section: Separating Seasonal and Inter-annual Changes In Surface Subsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inversion algorithm requires a sufficient number of interferograms to estimate an appropriate trend; however, the number of high-quality interferograms is often limited in some areas. Chen et al (2018b) first applied the PS-InSAR technique to ALOS/ PALSAR data to derive permafrost thaw subsidence in the Qinghai-Tibet Plateau with a rate ranging from 0.3 to 3 cm yr −1 using 17 scenes of ALOS. SAR images acquired during the snow-covered season were used in the study, which may include errors associated with snow accumulation.…”
Section: Separating Seasonal and Inter-annual Changes In Surface Subsmentioning
confidence: 99%
“…Synthetic aperture radar (SAR) interferometry (InSAR) is a processing technique for detecting surface displacements that has been widely used in applications such as crustal deformation (e.g., Massonnet et al 1993) and glacier motion (e.g., Joughin et al 2010). SAR data have been recently used to monitor permafrost's related deformations in Alaska (Liu et al 2010(Liu et al , 2015Iwahana et al 2016a), Canada (Short et al 2011(Short et al , 2014, Lena Delta (Antonova et al 2018;Chen et al 2018a;Strozzi et al 2018), and Tibet (Chen et al 2018b). Liu et al (2015) used the Advanced Land Observing Satellite/Phased Arraytype L-band Synthetic Aperture Radar (ALOS/PALSAR) InSAR to reveal the thermokarst settlement near Deadhorse along the North Slope, Alaska.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the global and seasonal temperature changes, without dominant scatter and phase variation, the backscattering and phase features of the ground targets in the permafrost region are significantly affected by spatial-temporal decorrelation, which obscures the underlying signal and limits the application of InSAR [19,20]. To reduce and overcome those limitations, MT-InSAR methods, including small baselines subset (SBAS) techniques [21], persistent scatter interferometry (PSI) techniques [22][23][24], and other PSI-and SBAS-like methods (Stanford method for persistent scatters (StaMPS) [19], temporally coherent point InSAR (TCP-InSAR) [25][26][27]) have been applied to numerous examples of surface displacement [12,[28][29][30]. Compared with conventional InSAR methods, MT-InSAR shows better performance in urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…The authors identified X-band backscatter time series as a useful tool complementing optical remote sensing and in situ monitoring for rapid analysis of tundra permafrost erosion along riverbanks and coastal areas. Chen et al [176] used Persistent Scatterer Interferometry (PSI) to map and quantify permafrost thaw subsidence in the Qinghai-Tibet Plateau. According to the authors, the PSI approach is less affected by temporal or geometric decorrelation, while their results indicated that permafrost areas near gullies are more vulnerable to gradual thawing and degradation.…”
Section: Surface Deformationmentioning
confidence: 99%